2005
DOI: 10.1021/ja052768v
|View full text |Cite
|
Sign up to set email alerts
|

Ti(IV) Binds to Human Serum Transferrin More Tightly Than Does Fe(III)

Abstract: The binding of titanium(IV) to human serum transferrin in 50 mM Tris with 20 mM bicarbonate and 10 mM citrate at pH 7.4 was studied by UV/vis kinetics and by isothermal titration calorimetry. Ti(IV) citrate, [Ti(C6H4O7)3]8-, employed in this study was previously characterized and delivers the metal to transferrin rapidly, allowing the quantification of the intrinsic binding constants for Ti(IV) to the C- and N-sites of transferrin. The results after correcting for blood plasma conditions (pH 7.4, [HCO3-] = 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 26 publications
9
103
1
Order By: Relevance
“…Both titanocene dichloride and Ti(IV) citrate rapidly deliver Ti(IV) to Tf (6, 9). In the case of Ti(IV) citrate, even in the presence of millimolar concentrations of free citrate, the exchange rate of Ti (IV) transfer to micromolar amounts of Tf is fast (9). We have already established that Ti 2 -Tf does not exhibit any cytotoxicity.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Both titanocene dichloride and Ti(IV) citrate rapidly deliver Ti(IV) to Tf (6, 9). In the case of Ti(IV) citrate, even in the presence of millimolar concentrations of free citrate, the exchange rate of Ti (IV) transfer to micromolar amounts of Tf is fast (9). We have already established that Ti 2 -Tf does not exhibit any cytotoxicity.…”
Section: Resultsmentioning
confidence: 87%
“…Evidence in support of this hypothesis is that Tf (which possesses two identical metal-binding sites) is only 39% Fe(III)-saturated (7) and can thus bind and transport other metal ions, typically hard metal ions (8). Ti(IV) has been shown to bind with very high affinity to Tf (9, 10), even higher than Fe(III) (9). In vivo studies have shown Ti(IV) to be endogenously bound to Tf (11).…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31] This protein leads to complete ligand stripping from the Ti IV core, and apparently allows somewhat selective cell penetration through the transferring receptors located more abundantly on tumor cell surfaces. Nevertheless, early loss of the most inert ligands abolishes their potential influence on the interaction with the biological target, and, thus, questions the contribution and influence of the particular ligand on the cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The binding to transferrin (Tf) is believed to play an important role in the mode of action of gallium salts as the binding constant is similar to Fe(III). Ga ions can bind to the two metal sites of Tf with binding constants log K 1 5 20.3 and log K 2 5 19.3, whereas Fe 31 -Tf-binding constants are slightly higher at log K 1 5 22.8 and log K 2 5 21.5 [15,20]. Gallium salts exhibit activity in malignant lymphomas and bladder cancer, and modest therapeutic potential in prostate, cervix and ovarian cancer in clinical trials [14,16,[21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%